EFFECTS OF PRÉCIS-WRITING ON STUDENTS’ RECOUNT WRITING AT ENGLISH LABORATORY OF UNIVERSITAS BANDAR LAMPUNG - Miftahul Jannah (ETNOLINGUAL, 2019)
Précis-writing is defined as the technique which engages the process of a précis which is a summary of a written composition (Bromly & Karen, 1983). Précis-writing technique facilitates the students to summarize reading texts by noting important points from the text and then use them in their writing. This study aims to find out whether précis-writing is more effective in improving students’ recount writing  than conventional teaching. Thirty of third level English laboratorystudents participated in this study. They were divided into two classes, the experimental class and the control class of 15 students respectively. They were trained during three meetings to apply précis-writing and conventional teaching for their recount writing. In the experimental class, the students received learning recount writing using précis-writing; while in the control class, the students received training of recount writing using conventional teaching. The data were collected through recount writing tests before and after the treatment. In order to see if précis-writing improved students recount writing, paired-samples t-test was conducted to students’ pretest and posttest scores in the experimental class. The result indicated that précis-writing significantly improved students recount writing. Furthermore, independent samples t-test analysis was also conducted to see if précis-writing implemented in the experimental class is more effective than conventional teaching implemented in the control class. The result showed that the significance value was       < .05 which means that précis-writing is more effective in improving students’ recount writing compared to the conventional teaching. Therefore, it can be concluded that précis-writing improved the students’ recount writing better than conventional teaching